2022
DOI: 10.19173/irrodl.v23i1.5717
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Among Self-efficacy, Utility Value, and the Community of Inquiry Framework in Preservice Teacher Education

Abstract: School closures during the COVID-19 pandemic have shown the importance of distance education, and teachers have been tasked with designing and delivering online courses in a short amount of time without much preparation or deliberation. As the future generation of teachers, preservice teachers need to be prepared to teach online, and their motivation to do so is a key factor in how successfully they do it. The community of inquiry framework provides researchers and practitioners with a framework for designing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…First, the role of the teaching profession in 'raising up generations' can be mentioned (e.g., De Cooman, De Gieter, Pepermans, Du Bois & Caers, 2007;Giersch, 2016;O'Brien & Schillaci, 2002;Watt & Richardson, 2007). At this point, teachers provide the acquisition of knowledge, skills and values that will help their students to be successful in their future lives and careers (Akcaoglu & Akcaoglu, 2022). However, by supporting their skills such as curiosity, creativity and critical thinking that will enable them to learn throughout their lives, they can help them become more resilient to ever-changing and, in a way, difficult life conditions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…First, the role of the teaching profession in 'raising up generations' can be mentioned (e.g., De Cooman, De Gieter, Pepermans, Du Bois & Caers, 2007;Giersch, 2016;O'Brien & Schillaci, 2002;Watt & Richardson, 2007). At this point, teachers provide the acquisition of knowledge, skills and values that will help their students to be successful in their future lives and careers (Akcaoglu & Akcaoglu, 2022). However, by supporting their skills such as curiosity, creativity and critical thinking that will enable them to learn throughout their lives, they can help them become more resilient to ever-changing and, in a way, difficult life conditions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Essentially, by having the experience of being an online learner, it would provide e teachers with a sense of empathy for the struggles that their own online students might face -which should enhance student learning (Bouton, 2016;Meyers et al, 2019). Additionally, Akcaoglu and Akcaoglu (2022) wrote that having teachers experience effective online learning would increase their own self-efficacy about teaching online, which according to Correy and Stella (2018) would also lead to greater student success.…”
Section: Recommendations For Teacher Preparationmentioning
confidence: 99%
“…However, with the depth of research, scholars have found that if the descriptive and explanatory power of the Community of Inquiry framework is to be enhanced, individual learner factors affecting learning should be added to the model, as individual factors directly affect the knowledge acquisition and cognitive engagement effects of students in the blended learning process (Shea and Bidjerano, 2010;Lan et al, 2018b). Some scholars have attempted to expand the framework in terms of individual positive psychological factors, and the results have shown that self-efficacy (Akcaoglu and Akcaoglu, 2022;Doo et al, 2023), self-regulation (Cho et al, 2017;Xue et al, 2023), motivation (Kilis and Yildirim, 2018;Zuo et al, 2022), and emotions (Espino et al, 2021;Sundgren et al, 2023) are related to the three presences in Community of Inquiry framework, but most of the above studies are limited to the theoretical level or online learning contexts, and it is still to be explored whether the individual-level positive psychological factors in blended learning contexts are related to the three presences in Community of Inquiry framework. Therefore, in this study, we hypothesize that personal-level positive psychological factors are a useful factor to extend the Community of Inquiry framework by attempting to more fully conceptualize the scope of presence in blended learning contexts.…”
Section: Introductionmentioning
confidence: 99%